Women's agency in the context of family networks in Indian diaspora - Jain, Shobhita (2006)
In diasporic settings, such issues as to who is a citizen, who can enter the family networks after obtaining which kind of visa are also located in "family" domains. Women in diasporas collaborate, acquiesce, co-opt and at times subvert the communication channels in family networks in order to negotiate economic hardships and gender-based oppresson. In the process they tend to either become victims or emerge as stronger, more empowered and innovative beings. - Reproduced.
Keywords: Non resident - Indians; Family - India; Women - India; Women